Improved Bacterial Foraging Algorithm for Optimum Economic Emission Dispatch with Wind Power - Sajjad Farajianpour; Ali Mohammadi; Saeed Tavakoli; S. Masoud Barakati (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In this paper, an improved bacterial foraging algorithm (IBFA) is employed to solve economic-emission dispatch (EED) problem. Regarding to more interest to renewable energy sources especially wind energy in recent years, it is necessary to use of incorporate wind power plants into EED problem. To consider realistic conditions, EED is included bi-objective of cost and NOx emission. The problems encountered with BFA are ineffective bacteria elimination resulted in poor performance. To overcome this, a modified BFA is proposed in reproduction step. EED is performed both with and without wind power plant subjected to couple of constraints using proposed approach and investigated from stand point of cost generation, and grid losses. Simulation results verify the accuracy of the proposed algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.851